Spatiotemporal distributions, co-occurrence networks, and assembly mechanisms of the bacterial community in sediments of the Yangtze River: comprehensive insights into abundant and rare taxa - Zhang, Guohua; Liu, Shufeng; Du, Wenran; Li, Yinghao; Wu, Zongzhi; Liu, Tang; Wang, Yichu (Frontiers in Microbiology, 2024)
Sediments are the key reservoir for rare bacterial biosphere that provide broad ecological services and resilience in riverine ecosystems. Compared with planktons, there is a lack of knowledge regarding the ecological differences between abundant and rare taxa in benthic bacteria along a large river. Here, we offered the comprehensive insights into spatiotemporal distributions, co-occurrence networks, and assembly processes of three divided categories such as always rare taxa (ART), conditionally rare taxa (CRT), and conditionally rare and abundant taxa (CRAT) in sediments covering a distance of 4,300 km in the Yangtze River. Our study demonstrated that ART/CRT contributed a lot to higher Chao-1 index, Shannon-Wiener index, and phylogenetic α-diversity of benthic bacteria in autumn than in spring. ART showed a higher overall beta-diversity and CRT/CRAT exhibited more significant distance-decay patterns than ART in both seasons mainly corresponding to macroscopic landform types. CRT predominated the nonrandom co-occurrence network with holding 97% of the keystone species mostly affiliated with Acidobacteriota flourishing in lower-reach plain. Two selection processes posed greater influences on the assembling of CRT (74.7-77.6%), while CRAT were primarily driven by dispersal limitation (74.9-86.8%) and ART were driven by heterogeneous selection (33.9-48.5%) and the undominated stochasticity (32.7-36.5%). Natural factors like river flow and channel slope had more significant correlations with community variations of all three groups than nutrients, and total organic carbon mediated the balance among distinct assembly processes of ART and CRT in both seasons. Taken together, this study provided a better ecological understanding of the discrepancy on biogeographic patterns 4 between abundant and rare bacterial taxa in sediments of Asia's largest river.